Sildenafil use in antidepressant drugs induced erectile dysfunction - Atmaca, Murad; Kulo?lu, Murat; Geçici, Ömer; Tezcan, A. Ertan (My University, 2001)
Objective: Sildenafil is a selective inhibitor of cGMP spesific phosphodiesterase type 5 which is the main isoenzyme responsible to metabolizing cyclic GMP in the penil corpus cavernosum. Sexual side effects are frequent, causing poor compliance and recently being considered effects of antidepressant treatment. In the present study, it was aimed to evaluate the efficacy of sildenafil on antidepressant induced erectile dysfunction. Method: Of twenty seven male patients who had applied to Psychiatry Department of Firat University Medical Faculty and been started on antidepressant drugs for any indication and experienced erectile dysfunction between October-August 2000, 18 who had not contraindication and accepted to study were included to this study. Sildenafil was started at 25 mg dose and increased to 50 and 100 mg doses. Erectile dysfunction before treatment and each dose was assessed by The International Index of Erectile Function (IIEF). Results: Of the patients, 14 (77.8%) improved. The most frequent side effects were flushing (n=3) and headache (n=2). Discussion: Our results demonstrate sildenafil to be efficacious and reliable in the treatment of erectile dysfunction.
Antidepresan i?laçlara ba?li erektil disfonksiyonda sildenafil kullanimi
Keywords: Antidepressant; Erectile dysfunction; Sildenafil